A cross sectional study on knowledge, attitude and behaviour regarding swine flu in urban slum of Hyderabad, India - Pattnaik, Snigdha; Khader, Rayyan Abdul (International Journal of Research in Medical Sciences, 2019)
Background: The study was conducted in the Urban slum area, Shekpet, Hyderabad, India which is the field practice area of Apollo Medical college. Methods: The aims was to study the awareness regarding symptoms, mode of spread and preventive measures of swine flu in the study population and to study the sources of information and health care seeking pattern of the population. Pre-designed questionnaire was used to collect information onsocio -demographic characteristics (age, sex, education and occupation), knowledge and awareness about the disease (nature, mode of spread/transmission, clinical features, preventive measures and precautions). Results: Majority were unaware of spread of Swine Flu from Pigs. 32% of them said it spreads through coughing and 27% through sneezing. About 15% of them said it spreads by sharing same room. Conclusions: The cross sectional study, was taken up during the recent outbreak of Swine flu in Hyderabad. Knowledge, Attitude and Prevention practices of the infection, was carried out in the urban slum of Shaikpet area the study will create awareness of the disease and its preventive measures among the people. Thus, it would reduce the incidence of occurrences of the disease in future.